Cortical and subcortical correlates of functional electrical stimulation of wrist extensor and flexor muscles revealed by fMRI - Blickenstorfer, Armin (Hum Brain Mapp, 2008)
The main scope of this study was to test the feasibility and reliability of FES in a MR‐environment. Functional Electrical Stimulation (FES) is used in the rehabilitation therapy of patients after stroke or spinal cord injury to improve their motor abilities. Its principle lies in applying repeated electrical stimulation to the relevant nerves or muscles for eliciting either isometric or concentric contractions of the treated muscles. In this study we report cerebral activation patterns in healthy subjects undergoing fMRI during FES stimulation. We stimulated the wrist extensor and flexor muscles in an alternating pattern while BOLD‐fMRI was recorded. We used both block and event‐related designs to demonstrate their feasibility for recording FES activation in the same cortical and subcortical areas. Six out of fifteen subjects repeated the experiment three times within the same session to control intraindividual variance. In both block and event‐related design, the analysis revealed an activation pattern comprising the contralateral primary motor cortex, primary somatosensory cortex and premotor cortex; the ipsilateral cerebellum; bilateral secondary somatosensory cortex, the supplementary motor area and anterior cingulate cortex. Within the same subjects we observed a consistent replication of the activation pattern shown in overlapping regions centered on the peak of activation. Similar time course within these regions were demonstrated in the event‐related design. Thus, both techniques demonstrate reliable activation of the sensorimotor network and eventually can be used for assessing plastic changes associated with FES rehabilitation treatment. Hum Brain Mapp, 2009. © 2008 Wiley‐Liss, Inc.